Analysis of System Operation Optimization In Steam Power Plants with the Lagrange Method - Aripriharta Aripriharta; Rafli Amirul Husain; Sujito Sujito; Mohamad Rodhi Faiz; Muchamad Wahyu Prasetyo; Arya Kusumawardana; Langlang Gumilar; Muhammad Afnan Habibi (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2024)
Steam Power Plant (PLTU) is a plant that relies on kinetic energy from hot steam to produce electrical energy. At the Paiton Power Plant, thermal energy is generated from burning a certain amount of coal. The use of coal-fired power plants still dominates most of the world's electricity supply. The optimal operation of electric power systems has grown in importance in recent years due to ever-increasing fuel costs. An electric power system basically consists of power generation units that aim to serve the needs of the load. Total production costs can be minimized by a combination of power loading on existing generating units so that an optimal load or more is obtained. This optimization process is called Economic Dispatch. Economic Dispatch has conducted a lot of research using various optimization methods. In this study, the optimization method to be used is the Lagrange method. Firefly algorithm and genetic algorithm methods are also used as performance comparisons. The results of this study show that the lagrange method can optimize generation costs with a difference of 243,227,475 / hour or 7,043% of the actual cost. While the firefly algorithm gets a difference of 243,227,471 / hour or 7.043% of the actual cost. And the genetic algorithm gets a cost difference of 242,119,792 / hour or 7,011% of the actual cost.